Pharmacogenetics of Pediatric Asthma: Current Perspectives - Perez-Garcia J; Espuela-Ortiz A; Lorenzo-Diaz F; Pino-Yanes M (Dove Medical Press, 2020)
Javier Perez-Garcia,1 Antonio Espuela-Ortiz,1 Fabian Lorenzo-Diaz,1,2 Maria Pino-Yanes1,3,4 1Genomics and Health Group, Department of Biochemistry, Microbiology, Cell Biology and Genetics, Universidad de La Laguna, San Cristóbal de La Laguna, Santa Cruz de Tenerife, Spain; 2Instituto Universitario de Enfermedades Tropicales y Salud Pública de Canarias (IUETSPC), Universidad de La Laguna, San Cristóbal de La Laguna, Santa Cruz de Tenerife, Spain; 3CIBER de Enfermedades Respiratorias, Instituto de Salud Carlos III, Madrid, Comunidad de Madrid, Spain; 4Instituto de Tecnologías Biomédicas (ITB), Universidad de La Laguna, San Cristóbal de La Laguna, Santa Cruz de Tenerife, SpainCorrespondence: Maria Pino-YanesGenomics and Health Group, Department of Biochemistry, Microbiology, Cell Biology and Genetics, Universidad de La Laguna, Apartado 456, San Cristóbal de La Laguna 38200, Santa Cruz de Tenerife, SpainTel +34 922316 502 – 6343Email mdelpino@ull.edu.esAbstract: Asthma is a chronic respiratory disease that affects 339 million people worldwide and has a considerable impact on the pediatric population. Asthma symptoms can be controlled by pharmacological treatment. However, some patients do not respond to therapy and continue suffering from symptoms, which impair the quality of life of patients and limit their daily activity. Genetic variation has been shown to have a role in treatment response. The aim of this review is to update the main findings described in pharmacogenetic studies of pediatric asthma published from January 1, 2018 to December 31, 2019. During this period, the response to short-acting beta-agonists and inhaled corticosteroids in childhood asthma has been evaluated by eleven candidate-gene studies, one meta-analysis of a candidate gene, and six pharmacogenomic studies. The findings have allowed validating the association of genes previously related to asthma treatment response (ADRB2, GSDMB, FCER2, VEGFA, SPAT2SL, ASB3, and COL2A1), and identifying novel associations (PRKG1, DNAH5, IL1RL1, CRISPLD2, MMP9, APOBEC3B-APOBEC3C, EDDM3B, and BBS9). However, some results are not consistent across studies, highlighting the need to conduct larger studies in diverse populations with more homogeneous definitions of treatment response. Once stronger evidence was established, genetic variants will have the potential to be applied in clinical practice as biomarkers of treatment response enhancing asthma management and improving the quality of life of asthma patients.Keywords: treatment response, short-acting beta-agonists, inhaled corticosteroids, candidate-gene studies, genome-wide association studies, whole-genome sequencing